On the Relationship and Interdependence Between Word Formation and Syntax - Балтова, Юлия (Slavic Languages Today: Categories, Structures and Processes, 2021)
The aim of this article is to track some important moments in the evolution of perceptions of the relation between syntax and word formation among European and Slavic linguists. The study considers the analysis of word composition and compounds by neogrammarians, the role of structuralism and the influence of modern linguistic theories on the development of contemporary word-formation theory, as well as modelling in studies of derivative lexical units.